Preferences predict who commits crime among young men - Thomas Epper; Ernst Fehr; Kristoffer Balle Hvidberg; Claus Thustrup Kreiner; Søren Leth-Petersen; Gregers Nytoft Rasmussen (Proceedings of the National Academy of Sciences, 2022)
Who commits crime? Theoretically, risk-tolerant and impatient people are more likely to commit crime because they care less about the risks of apprehension and punishment. By linking experimental data on risk tolerance and impatience of young men to administrative crime records, we find empirical support for this hypothesis. For example, crime rates are 8 to 10 percentage points higher for the most risk-tolerant people compared to the most risk averse. A theoretical implication is that those who are most prone to commit crime are also those who are least responsive to stricter law enforcement. Risk tolerance and impatience significantly predict property crime, while self-control is a stronger predictor of crimes of passion (violent, drug, and sexual offenses).
Keywords: 300